Modified Surgical Technique of Making Posteromedial Portal in Knee Arthroscopy Using a Radiofrequency Device - Pathak, Shirish (Arthrosc Tech, 2020)
In knee arthroscopy, a posteromedial portal is used for various indications including arthroscopic posterior cruciate ligament reconstruction, posterior cruciate ligament avulsion fracture fixation, posterior medial meniscal repair, medial ramp lesion repair, and synovectomy. Making the posteromedial portal is challenging for young and even experienced surgeons. Creating the posteromedial portal in knee arthroscopy is challenging and technically demanding for surgeons because of the thick muscular cover, proximity of the neurovascular bundle, tenacious tough capsule, and excessive fat deposition in the posteromedial knee and thigh region. Access for viewing the posteromedial compartment during different procedures is made simple, safe, and replicable with this technique of creating the posteromedial portal. This article describes a simple way to create the posteromedial portal using a radiofrequency device by a modified outside-in surgical technique.